Are Self-Presentation Influenced by Friendship-Contingent Self-Esteem and Fear Of Missing Out? - Salim, Frensen; Rahardjo, Wahyu; Tanaya, Titah; Qurani, Rahmah (Makara Human Behavior Studies in Asia, 2017)
One social media platform that is still highly favored by most people in this day and age is Instagram. Instagram users can present themselves in a visual form (eg, pictures and video) and text. Instagram promotes visual use, coupled with editing features which enable Instagram users to present themselves distinctly on social media. Friendship-contingent self-esteem is an important factor in presenting one's behavior in the context of friendly relations. However, there are negative impacts of use of social networking sites, such as lowering self-esteem, which is mediated by the fear of losing or fear of missing out (FoMO). This study aims to analyze the influence of friendship-contingent self-esteem and fear of missing out on self-presentation of Instagram users. Participants of this study were 326 male and female Instagram users spread across several provinces in Indonesia. This study uses Structural Equation Modeling (SEM) to construct an empirical model of friendship-contingent self-esteem, fear of missing out, and self-presentation which fits the data. Results show adequate goodness of fit, however, the only variable found to influence self-presentation was only fear of missing out. Friendship-contingent self-esteem was found to affect the fear of missing out, while friendship-contingent self-esteem did not affect self-presentation.